Cold Extraction of Carissa congesta Wight monitored by a comparative revision of HPLC and HPTLC - Doshi, Gaurav M.; Chaskar, Pratip K.; Zine, Sandeep; Une, Hemant D. (Pharmacognosy Communications)
Background: Carissa congesta is an important medicinal plant in India. Lupeol, an active constituent of this species, has been reported to possess good amount of pharmacological as well as therapeutic potential. Objective: In the current studies enlighten we focussed on determining the percentage of the lupeol present in the plant root extract by sophisticated analytical techniques. Materials and Methods: Shade-dried roots of Carissa congesta were subjected to a cold petroleum ether extraction followed by monitoring the lupeol contents by HPTLC and HPLC methods after carrying out preliminary phytochemical screening for the active constuients. Results: The extraction yield was found to be 1.8% (w/w). Phytochemical screening of the extract showed the presence of steroids, flavonoids, saponins, glycosides, tannins, phenolic compounds, fixed oils and fats.. The amount of lupeol present was found to be 25.80 % (w/w) and 11.18 % (w/v) by HPTLC quantification and HPLC analysis respectively. From HPLC analysis, the petroleum ether extract was found to a peak which eluted coincident with lupeol, indicating that the extract contained lupeol Conclusion: The extract contains significant amount of lupeol.
Keywords: Carissa congesta; Cold Extraction; HPLC; HPTLC; lupeol